PENINGKATAN PENGETAHUAN KEPALANGMERAHAN MELALUI LOMBA CERDAS CERMAT PADA ACARA JUMBARA PMR XIV PMI KOTA SEMARANG - Hadi, Syaikhul; Malik Ibrahim, Maulana (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2025)
This study aims to evaluate the effectiveness of quiz competitions as an interactive learning medium to enhance students’ knowledge and understanding, particularly regarding humanitarian (Red Cross) education. The analysis shows that quiz competitions effectively improve students’ comprehension of humanitarian principles. Through this approach, students not only strengthen their cognitive abilities in understanding Red Cross concepts but also develop humanitarian values, discipline, and social responsibility. The data reveal a significant improvement in participants’ understanding after the competition. Before the event, 83% of participants were in the low category, 4% in the fair category, and 13% in the good category. After the competition, 75% of participants reached the fair category, and 25% achieved the good category. Contributing factors to this improvement include adequate learning preparation, understanding of the material through quiz questions, and strong intrinsic motivation to achieve. Therefore, quiz competitions can serve as an innovative and effective learning strategy to strengthen students’ knowledge, attitudes, and character development in both primary and secondary education settings.